Effect of augmented corticotomy-assisted presurgical orthodontic treatment on alveolar bone fenestration and dehiscence in skeletal class III patients - Hui-Min Ma; Hang-Miao Lyu; Li Xu; Jian-Xia Hou; Xiao-Xia Wang; Wei-Ran Li; Xiao-Tong Li (Elsevier, 2023)
Background/purpose: Alveolar bone fenestration and dehiscence is common in untreated patients and potentially harmful. This study was to evaluate the effect of augmented corticotomy (AC) on the prevention and treatment of alveolar bone defects in skeletal class III high-angle patients during presurgical orthodontic treatment (POT). Materials and methods: Fifty patients with skeletal Class III high-angle malocclusion were enrolled, of whom 25 patients (G1) underwent traditional POT and 25 patients (G2) received AC during POT. The alveolar bone fenestration and dehiscence around the upper and lower anterior teeth were measured by CBCT. The incidence and transition of fenestration and dehiscence in the two groups were compared by the chisquare and Mann‒Whitney rank-sum tests. Results: Before treatment (T0), the incidence of fenestration and dehiscence around the anterior teeth of all patients was 39.24% and 24.10%, respectively. After POT (T1), the incidence of fenestration in G1 and G2 was 49.83% and 25.86%, respectively, and the incidence of dehiscence in G1 and G2 was 58.08% and 32.07%, respectively. For teeth without fenestration and dehiscence at T0, more anterior teeth in G1 exhibited fenestration and dehiscence at T1 than in G2. For teeth with fenestration and dehiscence at T0, most transitions in G1 were maintained or worsened, but "cure" cases were observed in G2. After POT, the cure rates of fenestration and dehiscence in G2 were 80.95% and 91.07%, respectively. Conclusion: During the POT of skeletal Class III high-angle patients, augmented corticotomy can significantly treat and prevent alveolar bone fenestration and dehiscence around anterior teeth.